The Critical Role of Timely Diagnosis in Preventing Complications: A Case Study of Matured Cataracts - Inayati, Aenun Azkiya; Joenianto, Heroe (Jurnal Ners, 2024)
Senile cataracts, prevalent in the elderly, especially in developing areas with limited healthcare access, pose significant challenges in geriatric patient management. This case study focuses on Mrs. S, a 66-year-old Indonesian woman with a mature-stage senile cataract, illustrating the difficulties in diagnosis and treatment in resource-constrained settings. Her symptoms, initially a white fog-like view, quickly worsened, highlighting the urgency of early cataract detection and intervention to prevent severe vision impairment. Examination revealed a uniformly cloudy lens in her right eye, leading to a diagnosis of Mature Stage Senile Cataract. The treatment plan included extracapsular cataract extraction with Intraocular Lens implantation. This case emphasizes the importance of early diagnosis in managing cataracts, the potential for less invasive surgical options with timely intervention, and the consequences of delayed diagnosis on patient well-being and treatment complexity. Early recognition and treatment are crucial in preserving visual function and minimizing complications associated with advanced cataracts, particularly in resource-limited healthcare settings.